Pemanfaatan Limbah Botol HDPE Sebagai Bahan Tambah Untuk Beton K-175 - Nasfadilla, Yolanda; Iswandi, Agung; Kamil, Firmanilah (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Plastic waste, especially HDPE, has a very long decomposition time and has the potential to pollute the environment. Therefore, this study aims to determine the effect and most optimal variation of the addition of plastic bottle waste on the compressive strength of K-175 quality concrete. The experimental method was used by testing materials and compressive strength of concrete at the Ketapang State Polytechnic Laboratory from May to August 2024. The test results showed that the average compressive strength of normal concrete based on conversion to 28-day age reached 176.37 kg/cm², while the compressive strength of concrete with HDPE variations decreased with values ranging from 124.95 kg/cm² to 152.60 kg/cm². Of the various variations tested, the mixture with 0.75% HDPE showed the best compressive strength results compared to other variations, with an average compressive strength based on conversion to 28 days of age of 152.60 kg/cm². Keyword: concrete compressive strength, HDPE plastic bottle waste, waste utilization